PERANCANGAN DAN IMPLEMENTASI APLIKASI PERPUSTAKAAN BERBASIS WEB UNTUK MEMPERMUDAH PENGELOLAAN DATA PERPUSTAKAAN DI SD NEGERI LEBAKWANGI - Alfa Rizki; Ariandra Febriyanto; Muhammad Dika Pratama; Khanif Faozi (Journal of Research and Publication Innovation, 2025)
This study aims to design a web-based library data management application to improve the efficiency of library operations at SD Negeri Lebakwangi. The project was initiated due to inefficiencies in the existing library data management system, such as errors in book record-keeping and difficulties in tracking book information. The development process adopted the System Development Life Cycle (SDLC) model with a Research and Development (R&D) approach. Data were collected through direct observation at the school, interviews with school personnel, and a review of relevant literature. The outcome of this research is a web-based library application designed to assist librarians and teachers in managing book data, monitoring book loans, and tracking student literacy activities more effectively. The system was developed using programming languages such as HTML, CSS (with Bootstrap), PHP, and JavaScript. The application includes features such as admin and user login, book and member management, circulation logging, and reporting. Test results show that the application successfully improves the efficiency and accuracy of library administration at SD Negeri Lebakwangi.